Economic Growth and Government Size in OIC Countries: A GMM Application - Dito Prakoso (SMART Insight, 2020)
This study intends to investigate the short and long-term relationship between government size and economic growth in the Islamic Cooperation Organization (OIC) during the 2010 to 2018 period through an empirical approach to 57 OIC countries using the dynamic data panel method GMM Arellano-Bond. The results show that in the short term, government size has a negative and significant effect on economic growth, while government investment has a positive and significant effect on economic growth. The results also show that in the long run, government size has a negative and significant effect on economic growth, while government investment has a positive and significant impact on economic growth. This research also supports the previous study which stated that there is a ‘inverted-U relationship’ between government size and economic growth. Policy recommendations that can be taken from this research are that the governments of OIC countries can make strategic steps in their spending by restructuring taxes and expenditures to maximize the effect on economic growth. Compared with previous research, the author tries to analyze the short and long-term relationship between government size and economic growth in OIC countries, by developing a longer research period and involving all OIC members, totaling 57 countries. This paper is expected to contribute to complementing the existing literature on economic growth in OIC countries